50% Ethanol extract of Orthosiphon stamineus modulates genotoxicity and clastogenicity induced by mitomycin C. (2nd January 2018) - Al-dualimi, Dhamraa Waleed; Shah Abdul Majid, Aman; Al-Shimary, Sarah Furqan Faisal; Al-Saadi, Amal Aziz; Al Zarzour, Raghdaa; Asif, Muhammad; Ein Oon, Chern; Abdul Majid, Amin Malik Shah
Abstract: Herbal products contain a variety of compounds which may be useful in protecting against cellular damage caused by mutagens. Orthosiphon stamineus ( O.s ) also known as Cat whiskers. The herb has been shown anti-oxidative properties and can modulate key cellular proteins that have cytoprotective effect. The study aimed to evaluate the effects of different doses (250, 500 and 1000 mg kg −1 ) of 50% ethanol extract of O.s (Et. O.s ) on micro-nucleated polychromatic erythrocytes (MNPCE), Polychromatic to normachromatic erythrocytes ratio (PCE/NCE), Mitotic index (MI), and Chromosomal aberration (CA) in Bab/c mice. Moreover, these parameters were used to evaluate the anti-genotoxic and clastogenic potencies of (Et. O.s ) against mitomycin c (MMC) that interact with biological molecules and induce genotoxic and clastogenic disorders in non-tumor cells. MMC (4 mg kg −1 ) was injected intraperitoneally (i.p.) to the mice before and after treatment with three different doses of (Et. O.s ). The results indicated that the extract at different doses did not show significant ( p ≥ 0.05) differences in (MNPCE), (PCE/NCE) ratios, and (CA) values. The higher doses sowed high (MI) values compared with untreated control group. MMC showed significant increase ( p ≤ 0.001) in (MNPCE), (CA) and reduce (PCE/NCE) and (MI) values compared with untreated control group. Treatment with (Et. O.s ) at different doses before and after MMC injection showed to modulate MNPCE, PCE/NCE ratios, CA and MI values in mice bone marrow cells suggesting genoprotective potential of this plant extract.